Pengaruh Modal, Kualitas SDM dan Promosi terhadap Keberhasilan Pemberdayaan UMKM Binaan Program Eduprintis UPRINTIS Indonesia - Lutfi Fida Lailia; Muhammad Alhada Fuadilah Habib (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
The success of good UMKM empowerment is certainly due to the factors that encourage this. Some factors that affect the success of UMKM empowerment are capital, quality of SDM and promotion. Capital assistance, providing education on the quality of SDM and promotional assistance provided by UPRINTIS Indonesia to UMKM actors through the Eduprintis Program that has been held have a positive impact on the success of UMKM empowerment. The purpose of this study is to determine the influence of capital, quality of SDM and promotion on the success of UMKM empowerment of the UPRINTIS Indonesia Eduprintis Program. This study used a quantitative approach with associative research type. The sampling technique used is quota sampling. The type of data used is primary data obtained from the distribution of questionnaires to UMKM actors assisted by the UPRINTIS Indonesia Eduprintis Program. The questionnaire data obtained were processed and analyzed using tests on SPSS16. The results showed that (1) capital, quality of SDM and promotion simultaneously affect the success of empowering UMKM assisted by the UPRINTIS Indonesia Eduprintis Program (2) capital has a positive effect on the success of empowering UMKM assisted by the UPRINTIS Indonesia Eduprintis Program (3) the quality SDM has a positive effect on the success of empowering UMKM assisted by the Eduprintis Program UPRINTIS Indonesia (4) promotion has a positive effect on the success of empowering UMKM assisted UPRINTIS Indonesia Eduprintis Program.